The Peruvian Fisherman's Knot A New, Simple, and Versatile Self-Locking Sliding Knot - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
Background: In many plastic surgery operations that are undertaken through relatively small incisions resulting in deep-seated operating fields, sliding knots with a self-locking property are preferred by plastic surgeons for 3 reasons: simplicity, reliability, and versatility. We describe a new and versatile sliding knot that can be easily sledded and locked. Methods: The technique of knot tying is described in detail as a stepwise approach with photographs. The main advantages of the Peruvian fisherman's knot are compared with other methods and summarized. Results: In addition to its adjustment-related properties, knot security has been adequate with this knot as evidenced by its clinical performance and the authors' experiences to date. Conclusion: The Peruvian fisherman's knot is especially useful while working in deep seated operating fields through a small incision. Tension created during knot tying is adjustable, which makes it an ideal choice for various lifting procedures in plastic surgery.
Keywords: Peruvian; fisherman's knot; sliding knot; self-locking; lifting; MECHANICAL PERFORMANCE; SUTURE MATERIAL; SURGICAL KNOTS; SURGERY; MONOFILAMENT; VOLUME